Humanist Approach as the Key to Successful Investigation of Terrorism Cases by Densus 88 - Priyanto, Sapto (Institute of Computer Science (IOCS), 2025)
Counter-terrorism efforts in Indonesia face significant challenges, including suspect resistance during investigations and resource limitations. This study analyzes the discretionary practices of Densus 88 AT Polri, particularly through humanistic approaches such as reuniting suspects with their families, granting communication access, and respecting spiritual needs. The findings show that humanistic discretion effectively enhances suspect cooperation, streamlines evidence collection, and strengthens legal legitimacy. This approach also upholds principles of justice and human rights. However, the implementation of discretion requires strict boundaries to ensure accountability and prevent abuse. A holistic strategy integrating repressive measures with humanistic approaches has proven successful not only in law enforcement but also in supporting the social reintegration of former terrorism convicts. This study recommends strengthening regulatory frameworks for discretionary practices to ensure effectiveness and alignment with human rights principles.